2021
DOI: 10.1371/journal.pone.0249647
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse midline gliomas, H3 K27M-mutant are associated with less peritumoral edema and contrast enhancement in comparison to glioblastomas, H3 K27M-wildtype of midline structures

Abstract: Purpose The entity ‘diffuse midline glioma, H3 K27M-mutant (DMG)’ was introduced in the revised 4th edition of the 2016 WHO classification of brain tumors. However, there are only a few reports on magnetic resonance imaging (MRI) of these tumors. Thus, we conducted a retrospective survey focused on MRI features of DMG compared to midline glioblastomas H3 K27M-wildtype (mGBM-H3wt). Methods We identified 24 DMG cases and 19 mGBM-H3wt patients as controls. After being retrospectively evaluated for microscopic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…In this study, both DMG (53.3 %) and GBM (64.3 %) were more common in males which is concordant with previous studies which showed a male preponderance in both DMG (54%) 8 and GBM (56.81%). 3,12 While previous studies showed that the most common location of DMG is the pons and that of GBM is in the temporal lobe, this study showed that the thalamus and frontal lobe are common locations for DMG and GBMs respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, both DMG (53.3 %) and GBM (64.3 %) were more common in males which is concordant with previous studies which showed a male preponderance in both DMG (54%) 8 and GBM (56.81%). 3,12 While previous studies showed that the most common location of DMG is the pons and that of GBM is in the temporal lobe, this study showed that the thalamus and frontal lobe are common locations for DMG and GBMs respectively.…”
Section: Discussionsupporting
confidence: 92%
“…This result is similar to that previously reported by other investigators which reported children and younger patients are more prone to DMG (mean age = 27 ± 13.8). 3,8 GBM usually occurs after the age of 40 years. 5,7,9,10 This study showed most patients with DMG were of 25 years or below age group, whereas the majority of GBMs were of above 50 years age group.…”
Section: Discussionmentioning
confidence: 99%
“…A significant difference in ADC, CBV, and CBF values (measured with the freehand regions of interest) has been reported between H3 K27M mutant and wild-type DMGs (28)(29)(30). Other studies found that several semantic and semiquantitative features on cMRI could be used to predict H3 K27M mutant status in DMG (31,32). But other non-radiomics studies using cMRI and DWI to predict H3 K27M mutant status showed converse results (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Three readers with neuroradiological experience for at least 7 years (RBr, AA, PR) independently judged the MRI data while blinded to each other's results. The following aspects were scored (adapted from Banan et al [18]): (1) location (thalamus, brainstem, vermis, cerebellum), (2) absence or presence of intratumoral necrosis, (3) degree of contrast enhancement in a four-step grading scheme of the intensity (strong, intermediate, low or absent), (4) presence of peritumoral edema, (5) presence of mass effect, (6) presence of rim enhancement and (7) occurrence of multifocal tumor manifestations. If a disagreement of the readers was noted, a consensus reading was performed in order to reach a final decision (based on majority).…”
Section: Mr Imaging and Analysismentioning
confidence: 99%
“…In a previous study from a singular neurosurgical institution, we analyzed the MRI signature of 24 DMGs and compared these with a series of 19 glioblastomas WHO grade IV, H3 K27M wildtype, of midline structures (midGBM-H3wt) [18]. We have now expanded this series, adding patients from a second institution, including the evaluation of the diffusion weighted imaging/apparent diffusion coefficient (DWI/ADC) pattern of our cases and controls as an additional criterion.…”
Section: Introductionmentioning
confidence: 99%